Evaluation of the Bone Thickness of Mandibular Molars using Cone Beam Computed Tomography - Nalbantoglu, Ahmet Mert; Yanık, Deniz (Journal of Dentistry Indonesia, 2021)
Objective: To investigate buccal and lingual bone thicknesses and fenestration rate of mandibular first and second molars using cone-beam computed tomography (CBCT). Methods: A total of CBCT images of 41 patients were selected and overall 120 mandibular molars were investigated. The buccal and lingual alveolar bone widths were measured at apex of the roots. The prevalence of fenestration in mandibular molars was recorded. Statistical analyses were performed. Results: The buccal bone widths of mesial root of second molars were significantly lower than the lingual (p<0.05). The lingual bone widths of mesial and distal root of second molars were lower than the buccal (p<0.05). The lowest thickness of buccal and lingual bone was observed in mesial root of first molar and distal root of second molar. The prevalence of fenestration in mandibular first and second molars was 5% and 10%. Conclusion: The buccal bone widths were lower at the first molar than the second molar. All fenestrations in first molar were in buccal aspect, in second molar were in lingual aspect. Topographical proximity of the buccal side of first molar and the lingual side of second molar to bone plate create a risky region for endodontic treatment or spread of infection.